Predicting tourists' intention to consume genetically modified food - Ramkissoon, Haywantee; Nunkoo, R. (Routledge, 2011)
The role which food plays in the tourism industry cannot be ignored. However, the literature has also led to believe that food risks are perceived to be higher abroad than at home and this could act as an impediment for the tourism industry. Though research on food as a tourism product has been growing in the literature, little has been said about genetically modified (GM) food intake by tourists. This study develops a model to predict tourists' intention to consume GM food based on the postulates of the theory of planned behavior. Attitude to GM food, perceived behavioral control, and subjective norms are proposed as the determinants of behavioral intention to consume such foods. The model also considers perceived risks with GM foods to be an important determinant of attitude. Furthermore, factors likely to be antecedents of the travelers' perceived risks with GM foods are discussed and incorporated in the proposed model. Some propositions on which future research could be based on are also made. The study concludes that the model is particularly useful for those destinations introducing GM foods in their markets and where the tourism industry plays an important role.